Individual Taxpayers Knowledge Analysis on Reporting with Separated Assets Status in the Annual Tax Return at Bekasi Madya Tax Office - Heru Sudinta; Krishantoro Krishantoro; Dwikora Harjo; Anny EkaYasika (Budapest International Research and Critics University, 2022)
Individual taxpayers with separated assets have difficulty reporting their annual tax return, and individual taxpayers who are husband and wife and have their own TINs must combine their net income at the time of annual tax return reporting, resulting in bigger progressive tax during the calculation of the income tax payable that leads to underpaid income tax. This research to analyze the knowledge of individual taxpayers with separated assets status on annual tax return reporting at the Intermediate Tax Office of Bekasi City, the obstacles faced, and the efforts made to overcome the obstacles. This research was conducted using descriptive qualitative methods. Data collection techniques interviews, observation and documentation. Knowledge and understanding of individual taxpayers with separate asset status in their annual tax reporting in the Intermediate Tax Office of Bekasi City, when measured by the theory of knowledge of taxpayers based on the Khasanah theory, is still low, and it affects the accuracy of the calculation during tax reporting.